Prediksi Tingkat Pertumbuhan Penduduk Menggunakan Metode Least Square Pada Desa Beringin Jaya Kec. Singingi Hilir Kab. Kuantan Singingi - Syafitri Syafitri; Rahyul Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The population of Beringin Jaya Village, Singingi Hilir Subdistrict, Kuantan Singingi Regency has increased every year. Forecasting is an important tool in effective and efficient planning. The Least Square Method is the most widely used method for determining of data trend equations because this method produces the result of prediction mathematically. The results of this forecasting are information of future population growth, so that they can be used by the Head of the Beringin Jaya Village to make decisions for improvy policy of life quality for the residents of that Village. One of them is how the results of this prediction can be used by the Village Head in planning programs to control the rate of population growth in the future. From the results of research by comparing the results of actual data with the results of prediction using the previous 11 years data has an accuracy value calculated using the Mean Absolute Percentage Error (MAPE) of 0.1431%. So, it is declared valid.Keywords : Forecasting, Population Growth, Least Square, Mean Absolute Percentage Error